Performance and Optimization of PT Slab Using Dynamic Load Condition of Larger Span Structure : A Review - Kuljinder Singh Munday; Vinay Singh Chandraker (International Journal of Scientific Research in Civil Engineering, 2021)
Many of the complex behaviours of reinforced cement concrete under shear and flexure are yet to be identified to employ this material advantageously and economically. The progress in the understanding and quantitative assessment of the behaviour of member subjected to flexure and shear has been less spectacular. The fundamental nature of shear and diagonal tension strength is not yet clearly understood. So, further basic research should be encountered to determine the mechanism, which results in shear failure of reinforced concrete members. The study presents the study of the behaviour of reinforced concrete deepbeam under seismic ( vibration) loading and the effect of shear reinforcement. The influence of variation of web reinforcement spacing (both vertical and horizontal) on the shear strength of general slab is investigated. The general trend in crack pattern, the load deflection characteristics and the mode of failure of R.C. slab under two-points loading are also investigated. In this study we are reviewing the literatures related to analysis of pt structures.